Eating (Meat) ethically: The convergence of Human Health, ecological sustainability - Chappe, de Leonval John (Department of Philosophy, 2023)
When discussing the ethics of what we eat, the key variables to take into account to form a robust position are human wellbeing, animal wellbeing, and ecological sustainability. I take this to be relatively uncontroversial. My contribution to this discussion is to note the manner in which questions relating to human health and ecology are often not discussed with sufficient precision and detail by vegetarian and vegan philosophers. Drawing on contemporary literature, I note the manner in which en masse vegetarianism/veganism is not a viable solution to the problem of how to eat ethically –– if we are to take seriously human health and survival in moral discussions; another point I take to be relatively uncontroversial. The core issue is that there are compelling reasons for granting that not all humans can survive or be healthy on vegetarianism/veganism. With this conclusion at hand, I then assess the manner in which two prominent existing moral theories on eating animals are radically altered such that they may grant the eating and farming of animals.